Dampak Sistem Pembayaran Non-Tunai Terhadap Permintaan Uang Kartal di Indonesia - Deswita Herlina; Safira Firdaus (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2022)
The stability of the demand for money is important to maintain the value of therupiah. This stability is seen in terms of the amount of currency and the ability ofmoney to fulfill all transactions in a short time. The use of non-cash money canhelp speed up the processing of financial transactions, but on the one hand it canhave an impact on changes in the demand for currency, which in turn affects thestability of the money supply. For this reason, it is necessary to conduct researchon the impact of using non-cash money on the demand for currency in Indonesia.This study analyzes the impact of non-cash payments using cards (APMK) on thedemand for currency in Indonesia for the 2014-2017 period. The analytical toolsused in this study are Vector Autoregression (VAR) to determine causality,Impulse Response Function (IRF) and Variance Decomposition (VD). The resultsshowed that the increase in the use of card-based non-cash money had an impacton reducing the demand for money in Indonesia in the 2014-2017 period. Thenon-cash money shock has an impact on the shock of changes in the demand forcurrency.